2011
DOI: 10.1007/bf03337746
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of formal voluntary work among older people. A review

Abstract: Background and aims: A narrative review of quantitative population-based longitudinal studies was conducted to examine the association of formal voluntary work and personal well-being among older people doing the voluntary work and those being served. Methods: To be included, the study had to be published in a peer-reviewed journal, written in English and conducted in Western countries, participants were at least 60 years of age, the study employed a longitudinal or experimental design, the methodology and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 45 publications
1
70
0
2
Order By: Relevance
“…The literature review indicated that each concept shared a positive relationship with health in older adults, regardless of the measure of health that was used. Longitudinal cohort studies further demonstrated that baseline social participation in any of the three forms is associated with better health outcomes at follow-up on several indices of health, including cognitive function, 39 depression, 34 better self-rated health and physical functioning, 59,63 and even a reduced incidence of falls. 35 We also examined evidence that the three concepts of social participation were associated, such that an increased number of connections increases the likelihood that the individual will also participate in more organised community activities associated with clubs and volunteer their time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature review indicated that each concept shared a positive relationship with health in older adults, regardless of the measure of health that was used. Longitudinal cohort studies further demonstrated that baseline social participation in any of the three forms is associated with better health outcomes at follow-up on several indices of health, including cognitive function, 39 depression, 34 better self-rated health and physical functioning, 59,63 and even a reduced incidence of falls. 35 We also examined evidence that the three concepts of social participation were associated, such that an increased number of connections increases the likelihood that the individual will also participate in more organised community activities associated with clubs and volunteer their time.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on older adults and volunteering have been conducted in the US. 12,59 A series of literature reviews has enumerated the benefits to older adults of volunteering. 12,57,59,60 Most studies report on the psychological and social benefits of volunteering, 12 although there is some research that demonstrates associations between volunteering and physical indicators of health.…”
Section: Volunteering and Health Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…185 Three other reviews examined relationships/associations between life changes more generally (including retirement) and physical activity. [186][187][188] A third group of relevant reviews considered populations of older adults (without referring to retirement) using a range of age inclusion criteria, 12,[189][190][191][192][193][194][195][196] with one specifically focusing on the potential benefits of voluntary work. 190 The first of the two other reviews of the retirement transition 1 examined 19 longitudinal or cross-sectional studies comparing retired adults with those not retired or longitudinal studies across the retirement transition (with no age parameters for inclusion set).…”
Section: Comparison Of Findings With Other Reviews In the Areamentioning
confidence: 99%